Ormeloxifene versus Tranexamic acid in dysfunctional uterine bleeding comparative evaluation - Hymavathi, Kaliki; Gottipati, Malini Devi; ., Prasuna; V., Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Dysfunctional Uterine bleeding (DUB) is the most common cause of abnormal uterine bleeding (AUB). Medical therapy being the first line of management, an ideal drug should be able to block the estrogenic effects on the Endometrium without interfering with its beneficial effects on other tissues. Both Ormeloxifene - a selective estrogen receptor modulator (SERM) and Tranexamic acid-an anti fibrinolytic inhibitor is important in the treatment of DUB. The aim of this study is to assess the efficacy and safety of Ormeloxifene v/s Tranexamic acid in the treatment of DUB. Methods: This is a prospective double blind study conducted for 2 years in 200 women presenting with DUB attending to the Gynaecology outpatient department (OPD) of Narayana Medical College and Hospital, Nellore, AP, India. Two hundred women presenting with DUB were recruited into this study (after fulfilling inclusion and exclusion criteria) with informed consent and randomly divided into two equal groups (Group-A and Group-B) after obtaining college ethical committee approval. Results: The reduction in the mean pictorial blood loss assessment chart (PBAC) score with Ormeloxifene (from 278 to 97.6) was significantly more than that of Tranexamic acid (from 261 to 134.5) at six months (p <0.0001). The rise in Hemoglobin concentration (8.4g% to 11.15g% vs. 8.5 to 9.7gm%; p <0.008) and reduction in Endometrial thickness (from 10.57mm to 6.5mm v/s 9.96mm to 7.24mm p <0.0001) were also significantly more with Ormeloxifene than with Tranexamic acid. Relief from dysmenorrhoea and subjective improvement were also found to be considerable with Ormeloxifene. Conclusions: Both Ormeloxifene and Tranexamic acid can be considered for DUB treatment but Ormeloxifene is found to be superior to Tranexamic acid in various aspects.